Market timing of seasoned equity offerings with long regulative process - Huang, Yong; Uchida, Konari; Zha, Daolin (Journal of Corporate Finance, 2016)
A long regulative process exists between the initial announcement and execution of seasoned equity offerings (SEOs) in China. Although the initial announcement of an SEO is associated with a significant reduction in the stock price, the regulator (China Securities Regulatory Commission) finally approves it after a significant run up in the price of the stock. Chinese managers execute SEOs after additional stock price increases. As a result, the stock price at issuance is not significantly different from the price on announcement, and is significantly higher than the price three months before the announcement. We also find stock prices decline following the execution. These results suggest that regulative screenings for market stabilization are beneficial for SEO market timing, and that Chinese managers successfully time the market, even with a prolonged regulative process.